Production and Characterization of Glucosamine from Bovine Synovial Fluid - ., Anwar; A, M; M A, El-hadi M (Gezira Journal of Health Sciences, 2013)
Objectives: Glucosamine is a natural aminomonosaccharide, which is a normal constituent of glycosaminoglycans in cartilage matrix and synovial fluid. Glucosamine has a role in the synthesis of cell membrane, collagen, osteoid, and bone matrix. The present work was undertaken to investigate bovine synovial fluid for the production of glucosamine. The method used for isolation of glucosamine included acid hydrolysis of the fluid. Results: The produced glucosamine (0.73-2.60%) had been purified and characterized by different identification methods that include: chemical colour tests; thin layer chromatography; C 18 - high performance liquid chromatography and infrared spectrophotometry compared to standard glucosamine. We can conclude that, there is an essential need for every body to produce and/or to take glucosamine supplements to stimulate the production of synovial fluid which lubricates cartilage and keeps joint healthy. This led to the fact that reliable analytical methods should be adopted for quality assessment of glucosamine commercial products used by consumers. In this research the investigated bovine synovial fluid was recognized to afford a considerable amount of glucosamine obtained by acid hydrolysis. Conclusions: The adopted and the described methods of analysis could be applied in qualitative and quantitative determination surveys of different supplement products containing glucosamine.